Effect of different grade levels of calcined clays on fresh and hardened properties of ternary-blended cementitious materials for 3D printing. (November 2020) - Chen, Yu; Romero Rodriguez, Claudia; Li, Zhenming; Chen, Boyu; Çopuroğlu, Oğuzhan; Schlangen, Erik
Abstract: This study aims to investigate the influences of different grades of calcined clay on 3D printability, compressive strength (7 days), and hydration of limestone and calcined clay-based cementitious materials. Calcined clays that contained various amounts of metakaolin were achieved by blending low-grade calcined clay (LGCC) and high-grade calcined clay (HGCC) in three different proportions. The results revealed that increasing the HGCC% ranging from 0 wt% to 50 wt% in calcined clay could: (1) increase the flow consistency; (2) impressively improve the buildability, and reduce the printability window of the fresh mixtures; (3) enhance and accelerate the cement hydration. However, increasing HGCC% led to an increase of air void content in the interface region of the printed sample, which weakened the compressive strength of the printed sample at 7 days. Besides, it confirmed that the cold-joint/weak interface was easily formed by using the fresh mixture with a high structuration rate.